FRET optofluidic microlasers enhance biological sensing - (:unkn) unknown (PENNWELL PUBL CO, 2016)
The marriage of liquid-based optical microcavities with engineered biological gain media using fluorescence resonance energy transfer (FRET) creates unique miniature lasers capable of ultra-sensitive biochemical detection.